Artificial intelligence and machine learning in 2D/3D medical image processing - Raja, Rohit (Boca Raton, FL : CRC Press, 2021)
"Medical image fusion is a process which merges information from multiple images of the same scene. The fused image provides appended information that can be utilized for more precise localization of abnormalities. The use of medical image processing databases will help to create and develop more accurate and diagnostic tools"--
OCLC-licensed vendor bibliographic record.
Keywords: Diagnostic imaging -- Data processing; Imaging systems in medicine